TANGGUNG JAWAB PARA PIHAK ATAS PELANGGARAN TERHADAP PRINSIP KETERBUKAAN PADA SAAT INITIAL PUBLIC OFFERING (IPO) - Masyhuri . (Fakultas Hukum Universitas Wahid Hasyim, 2012)
Public company is a company that can sell their stock to society. In implementation, Public company must do a principle of openness. Principle of opennes can be realized by providing the true and acurate information on various issues relating to the condition of the company. This kind of information contained in the prospectus at the time of IPO. It is important, because if the information submitted is not correct, then there will be a violation to the principle of opennes. All people that engage in capital market is the people who should be responsible in case of violation of the principle of opennes at the time of IPO. Kata kunci : Pelanggaran, Prinsip Keterbukaan, IPO